Faktor-faktor penentu kepuasan pengguna learning management system di program studi akuntansi Universitas Widyatama - Dianita, Mirna; Lestari Barus, Irene Sukma; Hidayat, Rachmat; Rachmawati, Rima; Rachman, Andry Arifian (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to identify the determinants of user satisfaction with a learning management system (LMS) in the Accounting Study Program of Widyatama University. The population in this study was students of the 2017–2021 accounting study program. The sample used was 194 people who were taken randomly. The data analysis technique used is covariance-based structural equation modeling. The results of the study stated that the implementation of e-learning lectures was more flexible; there was good support for the e-learning system; the technology used in e-learning lectures is acceptable; participants have high motivation in e-learning lectures; instructors have an important role in e-learning lectures; and participant achievement in e-learning lectures is very good. However, e-learning lectures have not been able to replace traditional (face-to-face) learning. And e-learning lectures have an effect on learning achievement.